2011
DOI: 10.2202/1547-7355.1772
|View full text |Cite
|
Sign up to set email alerts
|

Decisions in Disaster Recovery Operations: A Game Theoretic Perspective on Organization Cooperation

Abstract: Throughout history, disasters have had a defining impact on individuals, governments, and society as a whole. The terrorist attacks on September 11 th , 2001 and several catastrophic hurricanes in the gulf region have brought disaster response and emergency management to a new level of visibility and importance in the United States. The increased media coverage of international disasters, such as the Indian Ocean Tsunami in 2004 and the Earthquake in Haiti in 2010, have resulted in international disaster respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Rodriguez-Espindola, Albores, and Brewster [58] constructed a dynamic, multiobjective optimization model for humanitarian response operations incorporating multiple organizations but did not utilize game theory. Coles and Zhuang [10], earlier, discussed the potential of cooperative game theory in disaster recovery operations and provided a critique. Muggy and Heier Stamm [36] had also emphasized that cooperative models may assist in the identification of methods for partnering agencies to achieve greater impact than what is possible individually and independently.…”
Section: Game Theory and Humanitarian Operations In Disaster Reliefmentioning
confidence: 99%
“…Rodriguez-Espindola, Albores, and Brewster [58] constructed a dynamic, multiobjective optimization model for humanitarian response operations incorporating multiple organizations but did not utilize game theory. Coles and Zhuang [10], earlier, discussed the potential of cooperative game theory in disaster recovery operations and provided a critique. Muggy and Heier Stamm [36] had also emphasized that cooperative models may assist in the identification of methods for partnering agencies to achieve greater impact than what is possible individually and independently.…”
Section: Game Theory and Humanitarian Operations In Disaster Reliefmentioning
confidence: 99%
“…Gross () used game theory in a simulation to find responses to crisis from social networking sites. Coles and Zhuang () report a game theory study supported by the National Center for Risk and Economic Analysis of Terrorism Events to explore cooperative interaction between international and local agencies.…”
Section: Other Prior Researchmentioning
confidence: 99%
“…First of all, for shifting actual decisions to the desirable one, much research suggested normative solutions to change motive or related goals directly related to decisions (Ingram et al, 2006;Coles & Zhuang, 2011). Regarding the Sri Lankan government's decision on relocation, policymaker's recognition that forced relocation should be minimized by consultation with people, which can be one of the normative solutions.…”
Section: Conditions To Shift Decisionsmentioning
confidence: 99%
“…In terms of short-term recovery, Coles and Zhuang (2011) analyzed interactions between international and local players for relief resource utilization using game theory. Regarding long-term recovery, Keraminiyage (2011) evaluated the applicability of game theory concepts to housing reconstruction.…”
Section: Introductionmentioning
confidence: 99%